05 Nox2-derived oxidative stress and bone marrow-derived hematopoietic stem cell dysfunction in middle-age obesity. (20th November 2012) - Meijles, DN; Li, J-M
Abstract : Systematic oxidative stress is a characteristic of metabolic disorders and cardiovascular diseases associated with middle-age obesity. Bone marrow-derived multi-potent stem cells (BMSC) hold the hope in regenerating damaged tissues; however, the effect of oxidative stress on BMSC function remains unknown. In this study, we investigated the BMSC function in mouse models of middle-age obesity. Littermates of C57BL/J6 wild-type and Nox2 (an O2.–generating enzyme) knockout mice (7 m old, n=15) were fed with high fat diet (HFD, 45% kcal fat, 20% kcal protein and 35% kcal carbohydrate) or normal chow diet (NCD, 12% kcal fat, 28% kcal protein and 60% kcal carbohydrate) for 16 weeks. BMSCs were isolated from mice at 11 m of age. Compared to NCD controls, the numbers of CD133+/VEGFR2+ endothelial progenitor cells (EPC) were significantly decreased (2.2%±0.3 NCD vs. 0.8%±0.5 HFD) in HFD mice. There were significant increases (82±9.2 %) in the levels of O2.- production by HFD BMSC, and this was accompanied with accelerated cell proliferation (160±5.2%), cell cycle progression from G1/G0 phase to S phase, and significant increases in cell apoptosis (6.9±2.5% NCD vs. 29.8±8.2% HFD) as examined by annexin V flow cytometry. Moreover, the levels of PCNA and p53 expression were significantly increased in HFD BMSC. However, all these changes were absent in BMSC isolated from Nox2 knockout mice fed with HFD. In conclusion, an obesity environment activates Nox2 and oxidative stress damages BMSC function and reduces EPC population. Nox2 may present a therapeutic target for the prevention and treatment of obesity-related diseases.